To What Extent Do E-Trust and Perceived Risk Determine Use of Online Payment for Fast-Moving Consumer Goods? Evidence from a Systematic Review in the Moroccan Context - EL AIBI , Kawtar; HAMIDI , Lalla Saadia (Revue Internationale des Sciences de Gestion, 2026)
The development of e-commerce in Morocco confronts a persistent structural paradox: despite significant growth in digital infrastructure, mobile payment solutions, and regulatory frameworks for consumer protection, online transaction adoption particularly in the Fast-Moving Consumer Goods (FMCG) sector remains markedly below its potential. This paper presents a systematic literature review of the theoretical frameworks that account for this situation, focusing on the constructs of digital trust and perceived risk as determinants of online payment behaviour. Drawing on a corpus of 52 peer-reviewed publications selected through a PRISMA-compliant protocol, the review mobilises and critically interrogates the Technology Acceptance Model (TAM), the Theory of Planned Behaviour (TPB), the UTAUT2 model, and the multi-level trust frameworks developed in the marketing and information systems literatures. The review reveals three underexplored tensions in the current literature: the insufficiently theorised interaction between dispositional trust and institutional trust in weak-regulation contexts; the limited treatment of FMCG-specific risk dynamics, particularly the sensory evaluation gap; and the near-absence of research integrating fintech innovations mobile wallets, open banking into trust formation models for everyday consumer goods. An integrative conceptual model is proposed articulating cognitive, affective, and contextual determinants of online payment adoption in Morocco. The paper is situated within a positivist epistemological paradigm and proposes ten hypotheses that can be tested empirically and quantitatively validated in future research.